Fluorouracil Bolus Use in Infusional Regimens Among Oncologists—A Survey by Brazilian Group of Gastrointestinal Tumors. (August 2021) - Peixoto, Renata D.; Coutinho, Anelisa K.; Weschenfelder, Rui Fernando; Prolla, Gabriel; Rocha, Duilio; Andrade, Aline Chaves; Rego, Juliana Florinda; Fernandes, Gustavo dos Santos; Crosara, Marcela; Hoff, Paulo Marcelo; Dienstmann, Rodrigo; Costa e Silva, Matheus; et al.
Abstract : PURPOSE: The utility of administering fluorouracil (5-FU) in bolus in regimens of infusional 5-FU has been questioned. We aimed to quantify the use of 5-FU bolus in infusional regimens for gastrointestinal malignancies among Brazilian oncologists. METHODS: This was a cross-sectional electronic survey composed of eight multiple-choice questions sent to Brazilian oncologists during 14 days in February 2021. The survey instrument collected demographic data of participants and assessed practices in terms of 5-FU bolus use. We evaluated the association of demographic variables and 5-FU prescribing patterns with Fisher's exact test (odds ratio [OR]). RESULTS: The survey was completed by 332 medical oncologists. Overall, 37% were experienced oncologists and 32% were gastrointestinal specialists. In the first-line metastatic and in the adjuvant settings, 40% and 67% of oncologists always prescribe 5-FU bolus in infusional regimens, respectively. Experienced oncologists more frequently omit 5-FU bolus when compared with early-career oncologists, both in the metastatic (41% v 26%; OR, 1.98; P = .005) and adjuvant settings (28% v 14%; OR, 2.32; P = .003). In addition, more GI specialists remove 5-FU bolus when compared with generalists, but only in the metastatic setting (44% v 25%; OR, 2.33; P = .001). GI specialists are more likely to consider that treatment efficacy is not affected by 5-FU bolus withdrawal than are generalists (89% v 75%; OR, 2.65; P = .003). Most respondents (67%) keep leucovorin at the same doses when omitting 5-FU bolus, and only 16% always recommend dihydropyrimidine dehydrogenase testing. CONCLUSION: Our survey indicates that experience in oncology practice and percentage of time dedicated to treat GI cancers influence the prescription of 5-FU bolus in Brazil, with more frequent omission of it among experienced gastrointestinal specialists, particularly in the metastatic setting.